Effect of carrier type and concentration on the properties, anthocyanins and antioxidant activity of freeze-dried mao [Antidesma bunius (L.) Spreng] powders - Suravanichnirachorn, Wetanee; Haruthaithanasan, Vichai; Suwonsichon, Suntaree; Sukatta, Udomlak; Maneeboon, Thanapoom; Chantrapornchai, Withida (Agriculture and Natural Resources, 2018)
Mao fruit [Antidesma bunius (L.) Spreng] is an excellent source of anthocyanins, which are flavonoid pigments that provide a number of physiological benefits. Mao is a seasonal fruit and drying its juice has benefits in prolonging its shelf life, facilitating its transportation and extending the usage of mao powder. Freeze drying is a process widely used to produce fruit juice powders that are sensitive to heat in order to maintain their quality. A major problem in drying fruit juice is powder stickiness. In this research, drying carriers (maltodextrin and gum arabic at 25%, 30% or 35%) were added to improve the qualities of mao juice powder. The results showed that the addition of both carriers could improve the physical qualities of mao powders, and as the carrier concentration increased, the physical qualities increased, whereas the bioactivity qualities including the total anthocyanins content (TAC) and antioxidant activities tended to decrease. Powders with maltodextrin had better water solubility index and solubility time values than those of gum arabic. As a result, this work supported maltodextrin at 35% as a drying agent for mao powder production which produced a TAC of 2.63 mg/g and high-performance liquid chromatography determination indicated that the anthocyanins in the mao powder were delphinidin (1.10 mg/g) and cyanidin-3-O-glucoside (0.78 mg/g), with neither pelargonidin nor malvidin being detected.